A 3D geometrical consideration of path interval in filleted end milling - SEKINE, Tsutomu (Journal of the Japan Society for Abrasive Technology, 2016)
This study describes a 3-dimensional consideration of path interval in filleted end milling. Path interval is a machining condition able to adjust the balance between manufacturing efficiency and machined surface quality. In multi-axis filleted end milling, considering path interval it is practically essential to view the machining situation based on 3-dimensional geometry. However, only a few studies have been reported on the subject since the geometrical treatment is complicated. This study indicated that a point corresponding to a predetermined scallop height could be on a torus surface after a torus was modeled for the cutting edges of filleted end mill. A computational algorithm was proposed and verified to estimate the path interval in filleted end milling with tool inclination angle along the feed direction.